Multi-wavelength calibration procedure for the Pierre Auger Observatory fluorescence detectors - Rovero, Adrian Carlos (2009)
We present a method to measure the relative spectral response of the Pierre Auger Observatory Fluorescence Detector. The calibration was done at wavelengths of 320, 337, 355, 380 and 405 nm using an end-to-end technique in which the response of all detector components are combined in a single measurement. A xenon ﬂasher and notch-ﬁlters were used as the light source for the calibration device. The overall uncertainty is 5%.